2011
DOI: 10.1111/j.1526-4637.2011.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Pain with Botulinum Toxins—An Evidence-Based Review

Abstract: Evidence-based data indicate that administration of botulinum toxin in several human conditions can alleviate refractory pain. The problems with some study designs and toxin dosage are critically reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 89 publications
2
48
0
8
Order By: Relevance
“…Beneficial effects in pain have been reported in interstitial cystitis (Kuo, 2013, Russell et al, 2013, chronic arthritis (Chou et al, 2010), residual limb pain (Wu et al, 2012), different types of neuropathic pain (Ranoux et al, 2008;Zuniga et al, 2008) including diabetic neuropathy (Relja and Miletić, 2005;Yuan et al, 2009;Chen et al, 2013), masticatory pain etc. Although some double-blind, placebo controlled studies have been performed (review by Jabbari and Machado, 2011), clinical reports on BoNT/A effectiveness are dominated by studies based on a small number of patients or individual case reports. In the literature there is an increasing number of rare conditions with reported BoNT/A effectiveness on pain such as Parry Romberg syndrome (Borodic et al, 2013), Morton neuroma (Climent et al, 2013), painful legs and moving toes syndrome (Rodriguez and Fernandez, 2013), post-thoracotomy pain (Fabregat et al, 2013) post-amputation limb pain (Wu et al, 2012), etc.…”
Section: 2 Current Clinical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial effects in pain have been reported in interstitial cystitis (Kuo, 2013, Russell et al, 2013, chronic arthritis (Chou et al, 2010), residual limb pain (Wu et al, 2012), different types of neuropathic pain (Ranoux et al, 2008;Zuniga et al, 2008) including diabetic neuropathy (Relja and Miletić, 2005;Yuan et al, 2009;Chen et al, 2013), masticatory pain etc. Although some double-blind, placebo controlled studies have been performed (review by Jabbari and Machado, 2011), clinical reports on BoNT/A effectiveness are dominated by studies based on a small number of patients or individual case reports. In the literature there is an increasing number of rare conditions with reported BoNT/A effectiveness on pain such as Parry Romberg syndrome (Borodic et al, 2013), Morton neuroma (Climent et al, 2013), painful legs and moving toes syndrome (Rodriguez and Fernandez, 2013), post-thoracotomy pain (Fabregat et al, 2013) post-amputation limb pain (Wu et al, 2012), etc.…”
Section: 2 Current Clinical Experiencementioning
confidence: 99%
“…In addition to the small sample size and limited number of randomized controlled clinical trials, the reason for contradictory or negative findings can be the lack of standardized guidelines for BoNT/A application and dosage, and appropriate definition of study primary outcomes (Jabbari and Machado, 2011). …”
Section: 2 Current Clinical Experiencementioning
confidence: 99%
“…Apart from its effect on neuromuscular junction, recent preclinical and clinical studies reported the efficacy of BTX-A in reduction of allodynia and hyperalgesia in pain of different origins (Jabbari and Machado 2011;Pavone and Luvisetto, 2010). Moreover, BTX-A was recently registered for treatment of chronic migraine (Dodick et al, 2010) and several controlled clinical studies in other painful conditions are in progress (Jabbari and Machado, 2011;Singh, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BTX-A was recently registered for treatment of chronic migraine (Dodick et al, 2010) and several controlled clinical studies in other painful conditions are in progress (Jabbari and Machado, 2011;Singh, 2010). Importance of BTX-A application in clinical practice results from its unique ability to reduce pain in a long lasting manner (up to 6 months in humans).…”
Section: Introductionmentioning
confidence: 99%
“…This enables its therapeutic use in disorders characterized by overactive muscles, overactive exocrine glands and, most recently, non-muscular pain conditions (reviewed by Dressler, 2013, Matak and. Antinociceptive activity of BTX-A was demonstrated in various preclinical (reviewed by Pavone and Luvisetto, 2010) and clinical studies (reviewed by Jabbari and Machado, 2011) during the last decade. It was shown that a single injection reduces pain over a prolonged period of time (several months), which represents the unique feature of BTX-A among available analgesics.…”
Section: Introductionmentioning
confidence: 99%